What do we know about the future of agrobiodiversity in relation to food systems? - Cenacchi, Nicola; Gotor, Elisabetta; Petsakos, Athanasios; Schiek, Benjamin (International Food Policy Research Institute, 2025)
Agrobiodiversity — the diversity of living organisms that underpin agricultural systems — provides numerous critical benefits, from on-farm crop diversity and genetic resources that allow farmers to adapt crops to changing environments to the provision of ecosystem services such as pollination, disease and pest resistance, soil health, and water conservation. These benefits in turn support resilient livelihoods, food security, and diversified, nutritious diets.